Left main and triple vessel dissection 2 months postpartum. Issue 7 (18th January 2019) - Shahandeh, Negeen; Miyamoto, Michael I.; Tobis, Jonathan
Abstract: Spontaneous coronary artery dissection (SCAD) is a rare cause of acute coronary syndrome. The majority of cases reported in the literature involve a single vessel; multivessel and left main (LM) coronary artery involvement is rare. We present a case of triple vessel and LM SCAD in a postpartum patient and review the literature regarding percutaneous coronary intervention in the setting of SCAD.